2020
DOI: 10.1158/1055-9965.epi-20-0711
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Blockers Associated with Improved Breast Cancer Survival—A Nationwide Cohort Study from Finland

Abstract: Introduction: Breast cancer (BCa) has been associated with hypertension which might adversely affect disease prognosis. It is however unclear whether use of anti-HT drugs would improve BCa prognosis. Materials and Methods: A cohort of 73,170 women diagnosed BCa during 1995-2013 identified from the Finnish Cancer Registry and information on anti-HT drug use based on national prescription database during the same time period was combined. Anti-HT drug use was analysed separately by drug use before and after BCa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…Our primary nding is consistent with a number of previous studies indicating no signi cant association between BB use and BCD in their fully adjusted analyses [16,20,[22][23][24][25], while a number have found BBs to be protective [16][17][18], and one to increase the risk of BCD [26]. For example, a study of 466 breast cancer patients in England found hypertensive patients treated with BBs to have a 71% reduction in BCD (HR=0.29; 0.12-0.71) [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our primary nding is consistent with a number of previous studies indicating no signi cant association between BB use and BCD in their fully adjusted analyses [16,20,[22][23][24][25], while a number have found BBs to be protective [16][17][18], and one to increase the risk of BCD [26]. For example, a study of 466 breast cancer patients in England found hypertensive patients treated with BBs to have a 71% reduction in BCD (HR=0.29; 0.12-0.71) [17].…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of this evidence, several observational studies have been carried out, and some have reported that BB use may be protective for breast cancer-speci c death (BCD) [16][17][18][19]. However, others have noted no association between BBs and BCD [20][21][22][23][24][25], and one reported BBs were associated with an increased risk of BCD [26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that thiazide diuretics, but not other diuretics, were linked to an increasing risk of breast cancer, and the authors considered the increase in insulin resistance due to thiazide diuretics as a possible explanation ( Sarafidis et al, 2007 ; Ni et al, 2017 ). A recent study showed that the use of furosemide or other diuretics before breast cancer diagnosis increased the risk of breast cancer-related death ( Santala et al, 2020 ). Our results showed that the breast cancer mortality increased with the use of diuretics; however, we failed to analyze the effect of diuretic subtypes on breast cancer prognosis because there were few relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this evidence, several observational studies have been carried out, and some have reported that BB use may be protective for breast cancer-specific death (BCD) [16][17][18][19]. However, others have noted no association between BBs and BCD [20][21][22][23][24][25], and one reported BBs were associated with an increased risk of BCD [26]. The only RCT carried out on BBs (to date) found that preoperative propranolol downregulated biomarkers of invasive potential and inflammation, and improved biomarkers of cellular immune response [27].…”
Section: Introductionmentioning
confidence: 99%